Smartphone overuse and vision problems among university students - Dilshad S. Ismael (Zanco Journal of Pure and Applied Sciences, 2022)
The impact of smartphone on human health are still being tested and studied. This study estimates the effect of tiny screens of smartphones on eye defects such as myopia, Hyperopia, Astigmatism, Eye dryness and regarding the way which students in the college of science-Salahaddin University-Erbil use cellphones in their daily lives. In the first part of this study, the auto-refractometer device (21- 36111) have been used to test the eye refractive errors of 350 students (94 male,256 female). The student’s ages are about 18 (50 male,130 female) and 22 (44 male,126 female) years old and all the tests have been carried out at the medical physics laboratory in our department. Nearly, 46% and 40 % of the 18- and 22-years old students’ eyes respectively have been suffered from vision defects. In the second part, Schirmer's check was used to test dry eye disease (DED). Among 112 students, 27%, 16%, 28.5%, and 28.5% of students have normal, mild, moderate, and severe eye dryness respectively. Overall, according to the above results and questionnaire survey, the eye problems caused by the smartphone tiny screens are related to the time duration which an individual spends in front of the smartphone’s screen and also the operation mode of the smartphone. The way students use smart devices, as well as their exposure to blue light from mobile devices like smartphones and laptops, increases the risk of visual disorders including emmetropia, particularly astigmatism, and even permanent eye damage. References: - AKAR, A., KARAYIĞIT, M. Ö., BOLAT, D., GÜLTIKEN, M. E., YARIM, M. & CASTELLANI, G. 2013. Effects of low level electromagnetic field exposure at 2.45 GHz on rat cornea. International Journal of Radiation Biology, 89, 243-249. ARGILÉS, M., CARDONA, G., PÉREZ-CABRÉ, E. & RODRÍGUEZ, M. 2015. Blink rate and incomplete blinks in six different controlled hard-copy and electronic reading conditions. Investigative ophthalmology & visual science, 56, 6679-6685. ATAS, A. H. & ÇELIK, B. 2019. Smartphone use of university students: Patterns, purposes, and situations. Malaysian Online Journal of Educational Technology, 7, 59-70. BABABEKOVA, Y., ROSENFIELD, M., HUE, J. E. & HUANG, R. R. 2011. Font size and viewing distance of handheld smart phones. Optometry and Vision Science, 88, 795-797. BALCI, M., DEVRIM, E. & DURAK, I. 2007. Effects of mobile phones on oxidant/antioxidant balance in cornea and lens of rats. Current eye research, 32, 21-25. CARDONA, G., GARCÍA, C., SERÉS, C., VILASECA, M. & GISPETS, J. 2011. Blink rate, blink amplitude, and tear film integrity during dynamic visual display terminal tasks. Current eye research, 36, 190-197. CHOI, J. H., LI, Y., KIM, S. H., JIN, R., KIM, Y. H., CHOI, W., YOU, I. C. & YOON, K. C. 2018. The influences of smartphone use on the status of the tear film and ocular surface. PloS one, 13, e0206541. CIUFFREDA, K. J. & VASUDEVAN, B. 2008. Nearwork‐induced transient myopia (NITM) and permanent myopia–is there a link? Ophthalmic and Physiological Optics, 28, 103-114. CLAYTON, J. A. 2018. Dry eye. New England Journal of Medicine, 378, 2212-2223. DAVEY, S. & DAVEY, A. 2014. Assessment of smartphone addiction in Indian adolescents: a mixed method study by systematic-review and meta-analysis approach. International journal of preventive medicine, 5, 1500-1511. FOOK, C. Y., NARASUMAN, S., ABDUL AZIZ, N. & TAU HAN, C. 2021. Smartphone usage among university students. Asian Journal of University Education (AJUE), 7, 282-291. GROSS, H., BLECHINGER, F. & ACHTNER, B. 2008. Human eye. Handbook of Optical Systems: Volume 4: Survey of Optical Instruments, 4, 1-87. HARDELL, L. & SAGE, C. 2008. Biological effects from electromagnetic field exposure and public exposure standards. Biomedicine & pharmacotherapy, 62, 104-109. HIROTA, M., UOZATO, H., KAWAMORITA, T., SHIBATA, Y. & YAMAMOTO, S. 2013. Effect of incomplete blinking on tear film stability. Optometry and vision science, 90, 650-657. IVANOV, I. V., MAPPES, T., SCHAUPP, P., LAPPE, C. & WAHL, S. 2018. Ultraviolet radiation oxidative stress affects eye health. Journal of biophotonics, 11, e201700377. KIM, B.-H., HAN, S.-H., SHIN, Y. G., KIM, D. Y., PARK, J. Y., SIN, W. C. & YOON, J. H. 2012. Aided distance visual acuity and refractive error changes by using smartphone. Journal of Korean Ophthalmic Optics Society, 17, 305-309. KIM, D. J., LIM, C.-Y., GU, N. & PARK, C. Y. 2017. Visual fatigue induced by viewing a tablet computer with a high-resolution display. Korean Journal of Ophthalmology, 31, 388-393. KIM, J., HWANG, Y., KANG, S., KIM, M., KIM, T.-S., KIM, J., SEO, J., AHN, H., YOON, S. & YUN, J. P. 2016. Association between exposure to smartphones and ocular health in adolescents. Ophthalmic epidemiology, 23, 269-276. KOZLOWSKI, M. R. 2020. Blue light-induced retinal damage: a brief review and a proposal for examining the hypothetical causal link between person digital device use and retinal injury. Medical hypothesis, discovery & innovation in optometry, 1, 129-134. LEE, E. J. & KIM, H. 2019. Effect of Smartphone Use on Intraocular Pressure. Scientific Reports, 9, 1-7. LEE, H. S., CUI, L., LI, Y., CHOI, J. S., CHOI, J.-H., LI, Z., KIM, G. E., CHOI, W. & YOON, K. C. 2016a. Influence of light emitting diode-derived blue light overexposure on mouse ocular surface. PLoS One, 11, e0161041. LEE, H. S., PARK, S. W. & HEO, H. 2016b. Acute acquired comitant esotropia related to excessive Smartphone use. BMC ophthalmology, 16, 1-7. LEE, J.-B., KIM, S.-H., LEE, S.-C., KIM, H.-G., AHN, H.-G., LI, Z. & YOON, K. C. 2014. Blue light–induced oxidative stress in human corneal epithelial cells: protective effects of ethanol extracts of various medicinal plant mixtures. Investigative ophthalmology & visual science, 55, 4119-4127. LEITGEB, N. 2008. Mobile phones: are children at higher risk? Wiener Medizinische Wochenschrift, 158, 36-41. MOON, J. H., LEE, M. Y. & MOON, N. J. 2014. Association between video display terminal use and dry eye disease in school children. Journal of Pediatric Ophthalmology & Strabismus, 51, 87-92. NETO, A. R., ABRITA, M. B. & PARRÉ, J. L. 2017. THE INDUSTRY OF MOBILE PHONE DEVICES IN THE 2000s: ANALYSIS OF APPLE, NOKIA AND SAMSUNG INNOVATIVE PERFORMANCE BASED ON THE GAME THEORY. GEOFRONTER, 1, p. 71-95. NUHEL, A. 2021. Evolution of Smartphone PREETHI, J. & KOH, T. C., VICTOR 2019. BASIC ANATOMY OF THE EYE, ADNEXA AND VISUAL PATHWAYS. Essentials of Ophthalmology: For Medical School and Beyond. World Scientific. ROBERTS, J., YAYA, L. & MANOLIS, C. 2014. The invisible addiction: Cell-phone activities and addiction among male and female college students. Journal of behavioral addictions, 3, 254-265. ROOM, R. 2010. Use of Terms. The development of terminology concerning psychoactive substance use and disorders: the treaties, scheduling decisions and public health. . WHO, Agenda item 6.1. . ROSENFIELD, M. 2011. Computer vision syndrome: a review of ocular causes and potential treatments. Ophthalmic and Physiological Optics, 31, 502-515. SENCHYNA, M. & WAX, M. B. 2008. Quantitative assessment of tear production: A review of methods and utility in dry eye drug discovery. Journal of ocular biology, diseases, and informatics, 1, 1-6. SHARMA, B., KUMAR, P. & SHARMA, P. 2021. SMARTPHONE IS IT “BEHAVIOUR ADDICTION OR SUBSTANCE ABUSE DISORDER”: A REVIEW TO FIND CHEMISTRY BEHIND. International Journal of Pharmaceutical Sciences and Research, 12, 1000-1008. TSUBOTA, K. & NAKAMORI, K. 1995. Effects of ocular surface area and blink rate on tear dynamics. Archives of ophthalmology, 113, 155-158. UCHINO, M., YOKOI, N., UCHINO, Y., DOGRU, M., KAWASHIMA, M., KOMURO, A., SONOMURA, Y., KATO, H., KINOSHITA, S. & SCHAUMBERG, D. A. 2013. Prevalence of dry eye disease and its risk factors in visual display terminal users: the Osaka study. American journal of ophthalmology, 156, 759-766. e1. UPADHYAY, S. 2015. Myopia, hyperopia and astigmatism: a complete review with view of differentiation. Int. J. Sci. Res.(IJSR), 4. WALSH, K. 2009. UV radiation and the Eye. Optician, 237, 26-33. WONG, K. Y. 2010. Cell phones as mobile computing devices. IT professional, 12, 40-45. ZWINKELS, J. 2015. Light, electromagnetic spectrum. Encyclopedia of Color Science and Technology, 8071, 1-8.